Stress, Dietary Patterns and Cardiovascular Disease: A Mini-Review - Morera, Luis Pedro; Marchiori, Georgina Noel; Medrano, Leonardo Adrián; Defagó, María Daniela (Frontiers in Neuroscience, 2019)
According to the World Health Organization, an unhealthy diet and insufficient physical activity are the leading global risks to health. Dietary behavior is an important modifiable factor in cardiovascular disease (CVD) prevention. Furthermore, the fact that cardiovascular events and stress-related emotional disorders share a common epidemiology may indicate the existence of pathways linking these two diseases (JC Chauvet-Gelinier, ‎2017). Psychosocial stress can lead to changes in dietary patterns and under chronic stress conditions, high caloric and hyperpalatable foods are preferred. The interplay between these two factors impacts on several biological pathways: for example, it can prime the hippocampus to produce a potentiated neuroinflammatory response, generating memory deficits; it can also affect gut microbiota composition, ultimately influencing behavior and brain health and creating a predisposition to the development of diseases such as obesity, cardiovascular disease, diabetes and metabolic syndrome. Though both cognition and emotion can be heavily affected by caloric intake, diet composition and stress, the molecular mechanisms by which this occurs are still not clear. (Spencer, Laye, Korosi and Barrientos, 2017). In this review, we describe the interplay between stress and dietary patterns at a molecular level, and how these factors relate to brain health and mental fitness. Finally, we show how these findings could give rise to novel therapeutic targets for chronic diseases.